Evaluation and 3D imaging of mineral structure changes of the rabbit (New Zealand) skull during developmental periods - Kanmaz, Yesim Aslan; Baygeldi, Saime Betuel; Guezel, Baris Can; Yilmaz, Yuecehan; Karan, Meryem; Hark, Betuel Dagoglu; Yilmaz, Sadik (Wiley, 2024)
This study aimed to determine the morphometric measurements anatomically and CT images of skulls of healthy male and female rabbits during postnatal development, to analyse the data statistically and to demonstrate the structural changes in bone. A total of 40 rabbits (20 females and 20 males) were divided into four groups including prepubertal period (group I (0-1 month)), period between adolescence and adulthood (group II (3-5 month)) and later (young adult period as group III (1-3 years) and old adult period as group IV (3-5 years)), with five animals in each group. After the morphometric measurements, the surface area and volume values of the skull were calculated. The skulls were reconstructed using a 3D Slicer (5.0.2), which is used for 3D modelling. The cranial bones in each group were then crushed using a grinder so that the powdered samples were obtained for XRF (X-ray fluorescence technique). The p-value was statistically highly significant between group and gender (p < 0.001). In morphometric measurements, males were generally higher than females. Only PL, GBOC and GNB measurements were higher in females. The p-value between groups (in all measurements), between genders (in TL, GLN, FL, VL, OZB and GBN parameters) and between groups and genders (in TL, DL and VL parameters) was statistically highly significant (p < 0.001). The p-value between the groups, p-value between sexes and p-value between group and sex in Si, P, K, Ca, Ni, Zn, Sr, Sr and Ca/P elements were statistically significant (p < 0.001). Consequently, metric, volume and surface area measurements were taken through 3D modelling of skull bone in prepubertal period (group I), period between adolescence and adulthood (group II) and later (young adult period as group III and old adult period as group IV) of rabbits and the change in the mineral structure during postnatal development and effect of sex on this change were investigated. This might be the first study to assess both metric and mineral changes at four age intervals taken during the life span of rabbits.
Keywords: 3D imaging; mineral structure; morphometry; rabbit; skull; XRF